Opportunities for evaluation of sustainable tourism – assessing the availability of ETIS indicators in Poland - Niezgoda, Agnieszka (Turyzm/Tourism, 2023)
The purpose of the article is to evaluate the possibilities of evaluating sustainable tourism in Polish tourist regions, in particular, through the use of ETIS indicators and to assess for the availability of data for their calculation in the nationwide statistical system. Qualitative research methodology was used to study the availability of ETIS indicators. A diagnostic type research procedure was adopted and the desk research method was used. In a situation where the data necessary for calculating a given indicator was not found in the available sources, primary research in the form of direct interviews with representatives of branches of Statistical Offices was used. In order to quantify the availability of ETIS indicators, a system for their evaluation was adopted and aggregate indicators were proposed for the evaluation of sections and individual criteria in the section, which is the author’s attempt to develop a unified system for evaluating sustainable tourism indicators. The results of the study showed that the availability of data for calculating ETIS indicators in Poland is not satisfactory. The lowest rating was given to the availability of indicators that facilitate the management of the resort, including the tourists’ satisfaction survey (section A). Also rated very low was the availability of indicators of the environmental impact of tourism in a resort (section D). The results obtained confirm the results of studies by other authors dealing with the issue of the real use of ETIS in tourist regions of other countries.